Self-Efficacy and Readiness Towards Early Clinical Exposure Among Nursing Students - Kumalasari, Shinta Antin; Suparti, Sri; Raani, Kala (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: Early Clinical Exposure is a learning approach that integrates classroom learning with the clinical practice at the students' academic stage. Based on an interview with 3rd-semester Nursing Students, the results showed that they had low self-efficacy and readiness towards early clinical exposure. Objective: This study aims to evaluate self-efficacy and readiness towards early clinical exposure among nursing students of Universitas Muhammadiyah Purwokerto (UMP). The study design was a cross-sectional study involving 218 undergraduate students at a private Islamic university in their third semester. Methods: Data were collected using an online questionnaire of Google Form developed by the researcher, and the questions were valid and reliable based on a reliability test. The sampling method in this study was the total sampling technique. There were 50 questions of the item in the questionnaire and 6 items for demographic data. Result: The majority of pupils showed strong self-efficacy (98.2%) according to the findings of this study and moderate self-efficacy (1.8%). The majority of students presented high readiness (97.7%) and moderate readiness (2.3%). According to the correlation test results, a correlation (r = 0.545, p0.05) was found between self-efficacy and readiness for early clinical exposure. Conclusion: The higher the student's self-efficacy is, the more the readiness will be to face the practice of early clinical exposure.